Muros que não separam – a arte de rua em Manaus: a identidade indígena e sua representação em murais grafitados. - Oliveira, Glaunara Mendonça de (2018)
ABSTRACT The earliest human language records are in visual form and can be found on all continents caves walls. This fact reveal that representations through images painted on walls is inherent in human culture, which, by the generic concept, is attributed "The quality of the universal characteristic of all men and only of these" (BAUMAN, 2012, p 133). Therefore, there is no evidence of a pure culture, without interference from others. In this context of hybrid cultures, identities are displaced (HALL, 2015) through the ideologies propagation, which are "capable of providing the basis upon which individuals can shape a coherent identity" (EAGLETON 1997: 27). These ideologies are recognized in verbal discourses and in through multisemiotic resources, like artistic manifestations on city walls – the street art – which will be analyzed in this research. Street art redefines walls, because it brings together artists who collectively produce murals and also brings society and who are represented through this artistic manifestation, such as the indians painted on city walls, in Manaus, Amazonas. Based on these principles, it was possible, through this research, to unveil the manifest discourses in graffiti murals produced in Manaus urban spaces in which indigenous people are represented. This research purpose to critically demonstrate aspects related to these representations through the image about indigenous identity and culture also the relationship between indigenous people with the city and the environment. In order to meet this objective, four murals produced by Raí Campos and Rogério Soares were selected as corpus. As a methodology, the categories of Visual Design Grammar - VDG - were used, which defines that "visual structures do not reproduce only structures of the reality, but are linked to the interests of social institutions, and thus are ideological" (Kess, Van Leeuwen, 2006: 47), hence the need for a methodology that considers the discursive power of multisemiotic communication resources. The research was divided considering the processes of artistic production: The Outline, which is about the theoretical basis on which the analyzes are based; The Technique, in which the methodology and analytical categories used in the chosen corpus are presented; Finishing, which refers to the analyzes and data discussed; finally, The Final Art, in which the final considerations, limitations and suggestions for future research are presented. KEY WORDS: Street art. Graffiti murals. Indigenous people representations. Visual Design Grammar